2006
DOI: 10.1159/000094225
|View full text |Cite
|
Sign up to set email alerts
|

Duplications of proximal 16q flanked by heterochromatin are not euchromatic variants and show no evidence of heterochromatic position effect

Abstract: Extra euchromatic material was found within the major heterochromatic block of chromosome 16 (16qh) in one de novo case and seven members of two families. In contrast to the euchromatic variants of chromosome 9 (9qh), which are derived from pericentromeric euchromatin, molecular cytogenetics confirmed that these duplications were of 16q11.2→q12.2 in the de novo case, of 16q11.2→q13 in three members of family 1 and 16q11.2→q12.1 in four members of family 2. The duplication had arisen as a post-zygotic mitotic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…This is in contrast to the situation on chromosome 16, where duplications of unique sequence proximal 16q are found within the major heterochromatic block and are associated with developmental delay and behavioural problems. 24 Finally, we have confirmed the nature and extent of the duplications that underlie the 9p12 euchromatic variants of chromosome 9 which extend over the same area identified by Di Giacomo et al 10 It is interesting that the 9p12 amplification variants reported by Lecce et al 11 involve clones at both ends of the 9p12 duplication variant region ( Table 1). The pericentromeric region of chromosome 9 is thought to follow the 'domain' model established for chromosome 10 in which the centromere is surrounded by large alphoid repeat arrays which are themselves flanked by interchromosomally duplicated sequences which are, in turn, flanked by intrachromosomal duplications 25 .…”
Section: Discussionsupporting
confidence: 83%
“…This is in contrast to the situation on chromosome 16, where duplications of unique sequence proximal 16q are found within the major heterochromatic block and are associated with developmental delay and behavioural problems. 24 Finally, we have confirmed the nature and extent of the duplications that underlie the 9p12 euchromatic variants of chromosome 9 which extend over the same area identified by Di Giacomo et al 10 It is interesting that the 9p12 amplification variants reported by Lecce et al 11 involve clones at both ends of the 9p12 duplication variant region ( Table 1). The pericentromeric region of chromosome 9 is thought to follow the 'domain' model established for chromosome 10 in which the centromere is surrounded by large alphoid repeat arrays which are themselves flanked by interchromosomally duplicated sequences which are, in turn, flanked by intrachromosomal duplications 25 .…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, in families where 16q11-q13 derived euchromatic material was duplicated and inserted within the major heterochromatin block of chromosome 16 (16qh), there was no evidence for a heterochromatin position effect, i.e. repressed gene expression from the duplicated segment [Barber et al, 2006]. Alternatively, since a centromere is likely to associate with heterochromatin at the nuclear periphery, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In only a few of these cases the markers have been characterized extensively, however their content seems to be limited to the centromeric and heterochromatin regions. Trisomy involving band 16q12 is usually associated with clinical impact [for review see Barber et al, 2006]. It seems that individuals with duplications of this proximal 16q do not have characteristic facies but frequently have short stature, developmental and speech delay, learning difficulties and behavioral problems which range from mild to severe [Barber et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy involving band 16q12 is usually associated with clinical impact [for review see Barber et al, 2006]. It seems that individuals with duplications of this proximal 16q do not have characteristic facies but frequently have short stature, developmental and speech delay, learning difficulties and behavioral problems which range from mild to severe [Barber et al, 2006]. However, a recent report showed that not all euchromatic trisomies of 16q12 have a clinical repercussion [Rodrí-guez et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation